Dear Santa : A Novel - Macomber, Debbie (New York : Ballantine Books, 2021)
Feeling low after her boyfriend cheated on her, Lindy Carmichael heads home to Wenatchee, Washington, for Christmas where her mother encourages her to write a grown-up letter to Santa, which ultimately brings her hope and joy.
Keywords: Santa Claus -- (Fictitious character) -- Fiction; Mothers and daughters -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Wenatchee (Wash.) -- Fiction; Washington (State) -- Fiction; Romance fiction; Christmas fiction; Novels